2014
DOI: 10.1111/apt.12770
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exclusive enteral nutrition in the treatment of paediatric Crohn's disease: predictors of efficacy and outcome

Abstract: SUMMARY BackgroundExclusive enteral nutrition (EEN) induces remission and mucosal healing in children with active Crohn's disease (CD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 29 publications
3
65
0
8
Order By: Relevance
“…In the current study we observed that 80% of the patients were in clinical remission at week 12. This corroborates previous findings observed with this type of intervention [2,13,14].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study we observed that 80% of the patients were in clinical remission at week 12. This corroborates previous findings observed with this type of intervention [2,13,14].…”
Section: Discussionsupporting
confidence: 93%
“…The efficacy of EEN in the pediatric CD population is well established [2,4,12]. In this study the standard of care, which consists of EEN as the sole source of nutrition for up to 8 weeks, was provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…88 In some studies, early EEN is effective in inducing clinical, biochemical, and mucosal remission and improves outcomes at 1 year. [89][90][91] Although EEN has been successfully used and proven to be highly effective, it is often not preferred by patients due to the difficulty involved in administration. It may require tube feeding and typically consists of no food for 6 weeks.…”
Section: Dietary Recommendationsmentioning
confidence: 99%
“…The restrictive nature of EEN is difficult to maintain while targeted food elimination may be more sustainable. That genetic polymorphisms in the NOD2 gene are associated with differential outcomes in children with Crohn's disease treated with EEN supports the concept that individualization of dietary therapeutic approaches can improve outcomes [10].…”
mentioning
confidence: 72%